2022
DOI: 10.1002/rmv.2352
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive adjusted outcome data are needed to assess the impact of immune checkpoint inhibitors in cancer patients with COVID‐19: Results of a systematic review and meta‐analysis

Abstract: Background Determining how prior immune checkpoint inhibitor (ICI) therapy influences outcomes in cancer patients presenting with COVID‐19 is essential for patient management but must account for confounding variables. Methods We performed a systematic review and meta‐analysis of studies reporting adjusted effects of ICIs on survival, severe events, or hospitalisation in cancer patients with COVID‐19 based on variables including age, gender, diabetes mellitus, hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 82 publications
(294 reference statements)
1
5
0
Order By: Relevance
“…Based on ICIs’ potent immunostimulatory effects, an ongoing question since the SARS-CoV-2 outbreak has been whether recent therapy with the agents worsens, improves, or has no effect on outcomes in cancer patients presenting with COVID-19. In a systematic review of 42 observational clinical studies addressing this question, we found no clear impact of prior ICI therapy on survival, severe events, or hospitalization, but the level of evidence was very low due largely to limited adjusted outcome analysis in the studies ( 1 ).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Based on ICIs’ potent immunostimulatory effects, an ongoing question since the SARS-CoV-2 outbreak has been whether recent therapy with the agents worsens, improves, or has no effect on outcomes in cancer patients presenting with COVID-19. In a systematic review of 42 observational clinical studies addressing this question, we found no clear impact of prior ICI therapy on survival, severe events, or hospitalization, but the level of evidence was very low due largely to limited adjusted outcome analysis in the studies ( 1 ).…”
Section: Discussionmentioning
confidence: 85%
“…An ongoing question since the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak has been whether prior immune checkpoint inhibitor (ICI) therapy impacts outcomes in cancer patients with infection (coronavirus disease 2019, COVID-19) ( 1 ). ICIs counter the immunosuppressive effects that their targeted checkpoint molecules (e.g., PD-1 and PD-L1) exert on innate and adaptive immune responses, and they are highly effective for several cancer types ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Those outcomes can be attributed to the underlying neoplastic process and poor performance status of the patients, the side effects of specific anti-tumor agents, or the combination of the two [ 40 ]. Consequently, it is critical to decipher the interactions between COVID-19 infection and malignancy to successfully guide clinical decisions towards the best outcome for both pathologic conditions [ 41 ]. Large cohort studies have shown that recent cytotoxic chemotherapy leads to more COVID-19-related poor outcomes [ 42 , 43 ].…”
Section: Covid-19mentioning
confidence: 99%